Pengaruh Laporan Berkelanjutan, Green accounting Terhadap Kinerja Keuangan (Studi Empiris Pada Sektor Basic Material 2021 – 2023) - Tambunan, Ronia; Wahyuliza, Suci; Munthe, Inge Lengga Sari (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2025)
Indonesia is dedicated to attaining sustainable growth in line with the Sustainable Development Goals (SDGs). As a result, green accounting and sustainability disclosure reporting become essential. This study aimed to explore the influence of green accounting and sustainability reporting on the financial outcomes of companies within the basic materials sector that were publicly traded on the IDX from 2021 to 2023. For this research, the PROPER score was utilized to assess green accounting, while sustainable reporting was evaluated using the Global Reporting Initiative (GRI) and its 92 components, and financial performance was gauged through Return on Assets (ROA). The researcher employed multiple linear regression analysis, using SPSS 25 for data processing. The results of the study revealed a notable effect of sustainable reporting on financial performance. Conversely, green accounting did not show a significant influence on financial outcomes.